Cerebral and ocular toxoplasmosis related with IFN-γ, TNF-α, and IL-10 levels - Meira, Cristina S.; Pereira-Chioccola, Vera L.; Vidal, José E.; de Mattos, Cinara C. Brandão; Motoie, Gabriela; Costa-Silva, Thais A.; Gava, Ricardo; Frederico, Fábio B.; de Mattos, Luiz C.; , Toxoplasma Groups (Frontiers in Microbiology, 2014)
This study analyzed the synthesis of IFN-, TNF-α and IL-10 in chronically infected patients which developed the symptomatic disease as cerebral or ocular toxoplasmosis. Blood from 61 individuals were divided into four groups: Cerebral toxoplasmosis/AIDS patients (CT/AIDS group) (n=15), ocular toxoplasmosis patients (OT group) (n=23), chronic toxoplasmosis individuals (CHR group) (n=13) and healthy individuals (HI group) (n=10). OT, CHR and HI groups were HIV seronegative. The diagnosis was made by laboratorial (PCR and ELISA) and clinical subjects. For cytokine determination, peripheral blood mononuclear cells (PBMC) of each patient were isolated and stimulated in vitro with T. gondii antigen. IFN-γ, TNF-α, and IL10 activities were determined by ELISA. Patients from CT/AIDS and OT groups had low levels of IFN- when were compared with those from CHR group. These data suggest the low resistance to develop ocular lesions by the low ability to produce IFN- against the parasite. The same patients, which developed ocular or cerebral toxoplasmosis had higher TNF-α levels than CHR individuals. High TNF-α synthesis contribute to the inflammatory response and damage of the choroid and retina in OT patients and in AIDS patients caused a high inflammatory response as the TNF-α synthesis is not affected since monocytes are the major source this cytokine in response to soluble T. gondii antigens. IL-10 levels were almost similar in CT/AIDS and OT patients but low when compared with CHR individuals. The deviation to Th2 immune response including the production of anti-inflammatory cytokines, such as IL-10 may promote the parasite’s survival causing the tissue immune destruction. IL-10 production in T. gondii-infected brains may support the persistence of parasites as down-regulating the intracerebral immune response. All these indicate that OT and CT/AIDS patients produced low levels of IL10 (Th2 response) and IFN- (Th1 response). They produced high TNF-α suggesting a high inf